To Taste the River : poems - Bičole, Baiba (Plamen Press, 2021)
Baiba Bičole belongs to the postwar generation of Latvian poets living in exile who reached artistic maturity outside their native country and broke with the older exile generation's traditional, nationalistic poetry. In To Taste the River, Bičole's poems are lyrical and personal, often with intense emotion and startling imagery. This is Bičole's first collection of poems in English translation.